Neutrophil Extracellular Traps: A Perspective of Neuroinflammation and Complement Activation in Alzheimer’s Disease - Kretzschmar, Gabriela Canalli; Bumiller-Bini, Valéria; Gasparetto Filho, Miguel Angelo; Zonta, Yohan Ricci [UNESP]; Yu, Kaio Shu Tsyr [UNESP]; de Souza, Ricardo Lehtonen R.; Dias-Melicio, Luciane Alarcão [UNESP]; Boldt, Angelica Beate Winter (Frontiers, 2021)
Complement system (CS) components are associated with Alzheimer’s disease (AD), the commonest cause of dementia in the world. Neutrophils can be attracted to amyloid-β plaques by several pro-inflammatory factors, including the complement anaphylatoxin C5a. They may release neutrophil extracellular traps (NETs), which are chromatin nets associated with myeloperoxidase, elastase, and other enzymes. Some CS molecules, such as C5a, C1q, and CR1, are associated with increased neutrophil recruitment and NETs release. However, the relationship between CS molecules and NETs in AD is poorly understood. In this work, we detected higher NET concentrations in plasma and serum of Brazilian AD patients, than in elderly controls (medians = 2.78 [2.07–6.19] vs. 2.23 [0.33–4.14] ng/mL, p = 0.0005). We discussed these results within the context of our former findings on complement and AD and the context of the literature on complement and NET release, suggesting both as possible therapeutic targets to prevent the progress of the disease.
Keywords: Alzheimer's Disease; C1q; C5a; complement system; CR1; inflammation; neutrophil extracellular traps